Melanoma inhibitory activity in Brazilian patients with cutaneous melanoma - Macanori Odashiro; Gunter Hans Filho; Patricia Rusa Pereira; Ana Rita Coimbra Motta Castro; Alcione Cavalheiro Stief; Elenir Rose Jardim Cury Pontes; Alexandre Nakao Odashiro (Sociedade Brasileira de Dermatologia, 2015)
Abstract BACKGROUND: Melanoma inhibitory activity is a protein secreted by melanoma cells and has been used as a tumor marker. Increased Melanoma inhibitory activity serum levels are related to metastatic disease or tumor recurrence. Currently there are no studies on Melanoma inhibitory activity and cutaneous melanoma involving Brazilian patients. OBJECTIVE: To evaluate the performance and feasibility of measuring Melanoma inhibitory activity levels in Brazilian patients with cutaneous melanoma. METHODS: Blood was obtained from ten patients with proved metastatic cutaneous melanoma (Group 1), 15 patients resected for cutaneous melanoma without metastasis (Group 2) and 5 healthy donors (Group 3). Melanoma inhibitory activity was measured using a commercially available ELISA kit. RESULTS: There was a statistically significant difference of Melanoma inhibitory activity levels between patients with and without metastasis (p=0.002), and between patients with metastasis and healthy donors (p=0.002). There was no difference between patients without metastasis and healthy donors (p=0.443). CONCLUSION: Melanoma inhibitory activity is a tumor marker for cutaneous melanoma and the Melanoma inhibitory activity-ELISA test can be easily performed. Patients with metastasis have increased Melanoma inhibitory activity serum levels when compared to patients without metastasis and healthy donors.